外啮合齿轮泵的瞬时流量及脉动特性研究 - 刘茜 (Jixie chuandong)
The exiting volume of the pump is divided into two parts based on the principle of gear meshing and the control volume method,one part is formed by the involute curve,the other part is composed by the contact line formed by the movement of gear pairs.Instantaneous flow formula for the external gear pump is derived from the above analysis.And the necessary role of relief grooves is proven in reducing flow pulsation of the pump.Finally the impact of different design parameters including gear modulus,tooth number,pressure angle and addendum coefficient on flow characteristic of gear pump are discussed.